1992
DOI: 10.1002/pola.1992.080300826
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental aspect and behavior of saturated fluorocarbons in glow discharge in absence of potential source of hydrogen

Abstract: SYNOPSISThe glow discharge of a series of saturated fluorocarbons, CnF2n+2 ( n = 1, 2, 4, 6, and 8), was studied with glass substrates which do not contain any hydrogen. It was found that the deposition rate was a function of the F/C ratio of the starting fluorocarbons. That is, fluorocarbons with higher F/C ratio, such as CF, and C2Fs, hardly polymerized, while fluorocarbons with lower F / C ratio, such as C8FI8, polymerized as well as C2F4. After plasma exposure, the surface of glass substrate was characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
(1 reference statement)
2
34
0
Order By: Relevance
“…The details of cathodic polymerization were presented previously elsewhere. 13,14 It should be also emphasized that HFE is not a monomer of plasma polymerization in general sense, which does not form polymer in a hydrogen-free environment 15 but forms polymer in presence of hydrogen atoms either provided by the addition of hydrogen gas or from hydrocarbon substrates that contact with plasma. In this particular process of plasma polymerization of HFE on the surface of the plasma polymer of TMS, plasma polymerization of HFE occurred by utilization of hydrogen atoms existing on the surface of the TMS plasma polymer.…”
Section: Adhesion Failure Of the Plasma Polymer Of Tms To Aluminum Almentioning
confidence: 99%
“…The details of cathodic polymerization were presented previously elsewhere. 13,14 It should be also emphasized that HFE is not a monomer of plasma polymerization in general sense, which does not form polymer in a hydrogen-free environment 15 but forms polymer in presence of hydrogen atoms either provided by the addition of hydrogen gas or from hydrocarbon substrates that contact with plasma. In this particular process of plasma polymerization of HFE on the surface of the plasma polymer of TMS, plasma polymerization of HFE occurred by utilization of hydrogen atoms existing on the surface of the TMS plasma polymer.…”
Section: Adhesion Failure Of the Plasma Polymer Of Tms To Aluminum Almentioning
confidence: 99%
“…Several fundamental studies on characterization of CF 4 plasma-treated surfaces can be found in literature [13][14][15][16][17][18][19][20][21][22]. The major reactive components in CF 4 plasmas are reported to be F atoms and relatively low concentrations of CF n (n = 1, 2 and 3) radicals [13,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…C 3 F 8 is at the border. 8,9 The reason perfluorocarbons with higher F/C do not polymerize is that the F atom could be an etching species for hydrocarbon polymers as well as for silicon 10 and depress the polymerization. Therefore, as the number of fluorines decreases, the effectiveness of the polymerization increases.…”
Section: Introductionmentioning
confidence: 98%
“…They are CF 4 and C 2 F 6 , which are well-known as good etching gases for silicon. The classification of polymer forming and non-polymer forming for any perfluorocarbon can be done by its F/C ratio [5][6][7][8] ; ones with lower F/C ratios are polymer forming, and ones with higher F/C ratios, such as CF 4 and C 2 F 6 , are non-polymer forming. C 3 F 8 is at the border.…”
Section: Introductionmentioning
confidence: 99%